América. Itinerario de una revista de exilio. Entre giros políticos, socioculturales e históricos (1942-1946) - Rodríguez Martínez, María Isabel (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The interactions between bats and their ectoparasite insects are affected by various factors, among which are those related to the interacting ones and factors independent of these, such as changes in their habitat. The changes caused by these factors modify the interaction networks between these organisms by affecting both wealth, abundance and specialization among the interacting ones. Patterns in bat-insect ectoparasites interaction networks were studied at sites that present different types of management, in Lazaro Cardenas, Michoacán. The results indicate that the bat-insect ectoparasites interaction network in forest sites present a greater richness and abundance of species for both groups, in addition to presenting a high degree of specialization among their interacting subjects, observing a modular network where most of the species of ectoparasites insects showed interactions only within the module and with a species of bat. Regarding the cultivated site, the interactions within the network were less specialized, since the majority of the ectoparasitic insect species had interactions with more than one species of bat, therefore the modules within the network were less defined and have species of ectoparasite insects occurring in more than one module. The bat-ectoparasites insect interaction network formed at our modified site have less ectoparasites insect specialized to a single bat species, this due to the decline in perch sites, forcing bats to use the remaining sites and to coexist with different species of bats and ectoparasites insects, which promotes the appearance of new interactions and the decrease in the specialization of the interacting ones.

La experiencia del exilio en México había propiciado el surgimiento de diversos medios impresos que buscaban generar un espacio de difusión de ideas, producción artística e intelectual. Así, la actividad literaria y creativa que desempeñaron diversos grupos de pensadores mexicanos y españoles, permitió el surgimiento de una extensa red intelectual alrededor del continente, vinculada principalmente en torno a las revistas, como medio de expresión cultural y político. La revista cultural que aquí se estudia, llevó en sus inicios el nombre de América. Órgano de la juventud Hispanoamericana. Medio de expresión y divulgación de ideas creado por un grupo de jóvenes mexicanos y exiliados españoles pertenecientes a las juventudes socialistas de México y España. América puede ser vista como prueba fehaciente de que tanto los republicanos derrotados, como la juventud mexicana entendieron que hacía falta producir cul-tura, prolongarla, codificarla y discernirla para conectar el pasado, el presente y el incierto futuro.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2020-0479; Historia de América; Redes intelectuales; Hispanoamericanismo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2863